KERAGAMAN KARAKTER MORFOLOGI PLASMA NUTFAH GANYONG (CANNA EDULIS KERR.) - SUHARTINI, TINTIN; -, HADIATMI (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
Morphological Characters Diversity of Canna (Canna edulis kerr.) Germplasm. Edible canna (Canna edulis) is the source of potentially of foodstuf. Edible canna have high carbohydrate and nutritions. The starch of edible canna could be exploited as a food materials and industry. Evaluation and characterization were needed to get informations good characters of edible canna for genetic variability to get improved edible canna varieties. Indonesian Center of Agricultural Biotechnology and Genetic Resources and Development ( BB-Biogen) germplasm have two groups edible canna collection , they are red edible canna and white edible canna. The result showed the morphology characters of 27 edible canna accecions were not different on qualitative characters. Such as of 23 white edible canna have not different on qualitative characters. The red edible canna have red color on part of shoot, while in white edible canna have green color. The tuber of red edible canna have pink color and white color of white edible canna. The different are in the flower of white edible canna, there are 17 accecions have yellow color and 6 accecions have orange color. The quantitative characters of flowering, leaf length, leaf width, total leaf and leaf stalk length have low variability(cv <10 %). The character of plant hight, number of tiller per hill and tuber weight per hill have high coeficient variability with range of 14%-21%.
Keywords: diversity characters, morphology, edible canna (Canna edulis)